2005
DOI: 10.1128/aem.71.11.7008-7018.2005
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Community Dynamics and Polycyclic Aromatic Hydrocarbon Degradation during Bioremediation of Heavily Creosote-Contaminated Soil

Abstract: Bacterial community dynamics and biodegradation processes were examined in a highly creosote-contaminated soil undergoing a range of laboratory-based bioremediation treatments. The dynamics of the eubacterial community, the number of heterotrophs and polycyclic aromatic hydrocarbon (PAH) degraders, and the total petroleum hydrocarbon (TPH) and PAH concentrations were monitored during the bioremediation process. TPH and PAHs were significantly degraded in all treatments (72 to 79% and 83 to 87%, respectively), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

23
180
2
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 363 publications
(215 citation statements)
references
References 42 publications
23
180
2
3
Order By: Relevance
“…In recent years, the biodegradation of PAHs has received considerable attention and a variety of micro-organisms have been reported to play important roles in the process (Pothuluri & Cerniglia, 1994;Shuttleworth & Cerniglia, 1995;Kanaly & Harayama, 2000;Habe & Omori, 2003;Tortella et al, 2005). Bioremediation technologies have increasingly been proposed to decontaminate PAH-contaminated sites (Harayama, 1997;Samanta et al, 2002;Parrish et al, 2004;Vinas et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, the biodegradation of PAHs has received considerable attention and a variety of micro-organisms have been reported to play important roles in the process (Pothuluri & Cerniglia, 1994;Shuttleworth & Cerniglia, 1995;Kanaly & Harayama, 2000;Habe & Omori, 2003;Tortella et al, 2005). Bioremediation technologies have increasingly been proposed to decontaminate PAH-contaminated sites (Harayama, 1997;Samanta et al, 2002;Parrish et al, 2004;Vinas et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the biodegradation of PAHs has received considerable attention and a variety of micro-organisms have been reported to play important roles in the process (Pothuluri & Cerniglia, 1994;Shuttleworth & Cerniglia, 1995;Kanaly & Harayama, 2000;Habe & Omori, 2003;Tortella et al, 2005). Bioremediation technologies have increasingly been proposed to decontaminate PAH-contaminated sites (Harayama, 1997;Samanta et al, 2002;Parrish et al, 2004;Vinas et al, 2005).Phenanthrene, a PAH with three condensed rings fused in angular fashion, has a 'bay-region' and a 'K-region' and is often used as a model substrate for studies on the metabolism of carcinogenic PAHs. Over the last 60 years, a number of studies on phenanthrene degradation by several Gram-negative and Gram-positive bacterial species have been reported (Evans et al, 1965;Kiyohara et al, 1976Kiyohara et al, , 1982Kiyohara & Nagao, 1978;Barnsley, 1983;Gibson & Subramanian, 1984;Houghton & Shanley, 1994;Adachi et al, 1999;Samanta et al, 1999), where various pathways and metabolic diversity involved in phenanthrene degradation were documented.…”
mentioning
confidence: 99%
“…20 Another important group of clones belonged to Xanthomonas phylotype (4% of clones) which have been found as dominant group in bacterial community degrading aromatic hydrocarbons. 21 This study shows that identification of microbial diversity is a promising tool for the control of process performance.…”
Section: Operation With Partially Biodegradable Matter (Feed B)mentioning
confidence: 89%
“…As a result, substrate and nutrient diffusion are restricted and microbes become substrate limited. Holman and Tsang (1995) determined that a water content of 50-70 % of field capacity was optimum for biodegradation of aromatic hydrocarbons to proceed at maximum rate; also Viñas et al (2005) found that in a heavily creosote-contaminated soil, the higher percentage of hydrocarbon degradation was obtained with a 40-60 % of soil water-holding capacity (WHC), while with 20 % WHC, only slight degradation was observed. In our case, values near 20 % WHC (10 % of water content) drastically inhibited the phenanthrene biodegradation; when the moisture was increased, reached a 25 % WHC (15 % of water content), the soil biodegradation activity was recovered.…”
Section: Chemical Analysismentioning
confidence: 99%